The Influence of Entrepreneurial Orientation and Digital Transformation on Business Performance with Innovation Capability as a Mediating Variable in Fashion SMEs in Jakarta - Anetasya Angelica; Hendra Wiyanto (Brilliant International Journal Of Management And Tourism, 2025)
Micro, Small, and Medium Enterprises (MSMEs) fashion is one of the creative sectors that is experiencing rapid development in Jakarta. However, increasingly fierce competition, changing market trends, and digitalization require MSMEs to have an entrepreneurial orientation and adaptability through digital transformation. This study aims to analyze the effect of Entrepreneurial Orientation (EO) and Digital Transformation (DT) on Business Performance (BP) with Innovation Capability (IC) as a mediation variable. The study used a quantitative approach through a survey of 212 fashion MSME actors in Jakarta and analyzed using PLS-SEM. The results showed that EO and DT significantly positive effect on BP and IC. IC also has a significant positive effect on BP. However, IC does not mediate the relationship of EO to BP, but mediates the relationship of DT to BP. This finding confirms the importance of developing innovation and digital transformation capabilities in improving the performance of fashion MSMEs in Jakarta.